Meningkatkan Partisipasi dan Hasil Belajar Siswa pada Pembelajaran PKn dengan Materi Kasus Kasus Pelanggaran HAM dalam Rangka Perlindungan, Pemajuan dan Pemenuhan HAM melalui Model Pembelajaran Snowball Throwing di Kelas XI RPL 2 SMKN 4 Banjarmasin - Ma'al Abrar (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2015)
Causes of low participation and learning outcomes of students in grade 4 RPL 2 SMKN Banjarmasin is due to the use of teaching methods that have not been optimized in the implementation of learning, mostly mitode lecture and question and answer are often used in the implementation of learning. The purpose of this research is: (1) Want to know the model Snowball rowing on track with the learning material cases of human rights violations in order to protect, promote and fulfill human rights in class XI RPL 2 SMKN 4 Banjarmasin. (2) Want to know students' participation in the learning track with cases of human rights violations in the context of the protection, promotion and fulfillment of human rights through the learning model Snowball rowing in class XI RPL 2 SMKN 4 Banjarmasin. (3) Want to know the results of students in the learning track with material cases of human rights violations in the context of the protection, promotion and fulfillment of human rights through the learning model Snowball rowing in class XI RPL 2 SMKN 4 Banjarmasin. To achieve these objectives, action research conducted in two cycles, and each cycle consisting of three meetings. Data collection was performed using the test and non-test. Tests conducted with a series of questionnaires to students and non tests done through observation, interviews, documentation and library.These results demonstrate the applicability of the model of rowing Snowball was in accordance with the planned management and learning is done by teachers, including the qualifications either. Participation of students and teachers in the learning civics model of learning rowing Snowball was in accordance with aspects of the cooperative and is included in both the qualification. Civics student learning outcomes after using the classical model of learning and increased Snowball rowing is good in qualifying.Teachers are expected to be able to make a model of Snowball rowing as an alternative in efforts to increase the participation and student learning outcomes, due to the implementation of the model Snowball Rowing good then learning will be more effective and efficient.Keywords : Participation, learning outcomes and learning Snowball rowing